A method to determine the strain of the AlGaN barrier layer under the gate in AlGaN/AlN/GaN heterostructure field-effect transistors. (March 2015) - Zhao, Jingtao; Lin, Zhaojun; Luan, Chongbiao; Chen, Quanyou; Yang, Ming; Zhou, Yang; Lv, Yuanjie; Feng, Zhihong
Graphical abstract: Compared with the side-Ohmic contact processing, the normal-Ohmic contact processing greatly affects the strain of the AlGaN barrier layer. Highlights: We present a method to determine the strain of the AlGaN barrier layer. The normal-Ohmic contact processing greatly affected the strain of the AlGaN barrier layer. The strain of the AlGaN barrier layer was weakly affected by the side-Ohmic contact processing. Abstract: Based on the forward current–voltage ( I – V ) characteristics and the capacitance–voltage ( C – V ) curves between the gate and source, a method to determine the strain of the AlGaN barrier layer under the gate in AlGaN/AlN/GaN heterostructure field-effect transistors (HFETs) has been presented. With this proposed method, the strain of the AlGaN barrier layer for the prepared AlGaN/AlN/GaN HFETs with the normal-Ohmic contacts and the side-Ohmic contacts has been analyzed and determined. It was found that the normal-Ohmic contact processing greatly affected the strain of the AlGaN barrier layer and the tensile strain of the AlGaN barrier layer was gradually reduced from the middle to the Ohmic contacts for the AlGaN/AlN/GaN HFETs with the normal-Ohmic contacts, while the strain of the AlGaN barrier layer was weakly affected by the side-Ohmic contact processing.